RETRACTED: Glucocorticoids Should Be Used With Caution in Patients With SARS-CoV-2 - Guo, Yong; Chen, Yan; Li, Yingchuan (Frontiers in Medicine, 2021)
COVID-19 has become a global pandemic and the use of glucocorticoid in clinical practice is also controversial. Our clinical experiences of glucocorticoid treatment suggested that some cases were effective, others were ineffective and even potential immunosuppression could lead to deterioration. Therefore, it should be used with caution in patients with COVID-19.